2012
DOI: 10.1016/j.expthermflusci.2012.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the double ramp in hypersonic flow using luminescent measurement systems

Abstract: Compression ramp flows in supersonic and hypersonic environments present unique flow patterns for shock wave-boundary layer interaction studies. They also represent the generic geometry of two-dimensional inlets and deflected control surfaces for re-entry vehicles. Therefore, a detailed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Relatively small changes in terms of the normalised intensity ratio are observed in both the PtTFPP and Ru (II) polymer-based PSPs when the temperature ratio is approaching T/T ref = 1. In fact, a similar phenomenon was also documented in the studies conducted by Yang et al [13] and Gongora-Orozco et al [35]. However, the authors in [13] and [35] did not explain the reasons that might lead to the occurrence of this phenomenon.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Relatively small changes in terms of the normalised intensity ratio are observed in both the PtTFPP and Ru (II) polymer-based PSPs when the temperature ratio is approaching T/T ref = 1. In fact, a similar phenomenon was also documented in the studies conducted by Yang et al [13] and Gongora-Orozco et al [35]. However, the authors in [13] and [35] did not explain the reasons that might lead to the occurrence of this phenomenon.…”
Section: Resultssupporting
confidence: 67%
“…In fact, a similar phenomenon was also documented in the studies conducted by Yang et al [13] and Gongora-Orozco et al [35]. However, the authors in [13] and [35] did not explain the reasons that might lead to the occurrence of this phenomenon. Similar to the pressure sensitivity, the gradient of the plotted lines in Figure 7 shows the temperature sensitivity of the two polymer-based PSPs being studied.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Recent studies [49] have allowed the investigation of Göertler vortices for hypersonic Mach numbers as well as the development of measurement techniques [50,51].…”
Section: Umist Hst2 Hypersonic Shock Tunnelmentioning
confidence: 99%
“…[32][33][34][35][36][37] The in-house developed PSP technology used in the present study has been successfully applied in a variety of flow conditions and has been found in all cases to provide accurate pressure measurements when compared to conventional pressure transducers. [38][39][40][41][42][43][44] The PSP setup consists of a LaVision Image Intense 12-bit CCD camera with a 590nm long-pass filter mounted on the lens, and UV LEDs with peak wavelength of 390nm were used for image acquisition. Ruthenium is used as the luminohpore molecules in the current recipe.…”
Section: B Measurement Techniquesmentioning
confidence: 99%